Penerapan Model Pembelajaran Student Facilitator and Explaining untuk Meningkatkan Hasil Belajar Siswa Sekolah Menengah Kejuruan - Habibullah, Habibullah; Angraini, Rezi (Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to analyze the improvement in students' learning outcomes and the percentage of mastery learning after implementing the Student Facilitator and Explaining learning model in the Electrical Installation subject at SMK Negeri 1 Sumatera Barat. This research employs a pre-experimental method with a One-Group Pretest-Posttest design. The research subjects are 30 students of class XI TITL 1 at SMK Negeri 1 Sumatera Barat for the 2024/2025 academic year. Data collection was carried out through pretest and posttest questions that had been validated by experts in the field. Before the implementation of the learning model, students were given a pretest (initial test), while a posttest (final test) was administered after the learning process was completed. The research results indicate that the implementation of the Student Facilitator and Explaining model in the Electrical Installation subject can improve students' learning outcomes. This improvement is evident in the cognitive aspect, as shown by the analysis of pretest and posttest scores using the N-Gain Score formula, which yielded a value of 0.66, categorized as moderate. The percentage of mastery learning also experienced a significant increase, with 90% of students successfully achieving the Minimum Competency Criteria. Thus, the Student Facilitator and Explaining learning model is effective in enhancing students' learning outcomes in the Electrical power Installation subject.